Kepuasan Pelanggan berdasarkan Dimensi Timeliness Kualitas Jasa Evans dan Lindsay dengan Metode Importance Performance Analysis - Puput Hermanti (Universitas Airlangga, 2017)
Based on Keputusan Menteri Pendayagunaan Aparatur Negara Nomor KEP/25/M.PAN/2004 level of customer satisfaction of a service can be judged by the Community Satisfaction Index, there are fourteen elements of these services have a standard that is equal to 85%. General clinic and specialist in Menur Mental Hospital Surabaya has a Community Satisfaction Index by 75.11% which is below the standard of 85%. This research was purposed to analyzing customer satisfaction based on the level of importance of hospital performance in timeliness dimension of Evans and Lindsay service quality with importance performance analysis method. The research design was observational with cross sectional approach. Research conducted on November 2016 included 98 customer in General clinic and Specialist in Menur Mental Hospital Surabaya as respondents. Data were analyzed by Importance Performance Analysis. The result showed respondents considered that all aspects of the timeliness dimension is very important, especially for check the wait time ≤ 60 minutes aspect with mean importance value is 3.58, and performance service respondents considered check wait time ≤ 60 minutes aspect had smaller mean value performance (2.44) from the mean performance timeliness (2.84). The conclusion is customer not satisfied with timeliness dimension of Evans and Lindsay service quality. Keywords: Customer Satisfaction, Importance-Performance Analysis, Timeliness